Pengaruh Model Project Based Learning dan Motivasi Belajar Terhadap Hasil Belajar IPS Siswa di SD - Paska Sriulina Tarigan (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
This study aims to determine: (1) The difference in learning outcomes between groups of students taught using the Project Based Learning model and groups of students taught using the expository model; (2) The difference in learning outcomes between groups of students who have high learning motivation who are taught using the Project Based Learning model and groups of students who have high learningmotivation who are taught using the expository model; (3) The difference in learning outcomes between groups of students who have low learning motivation who are taught using the Project Based Learning model and groups of students who have low learning motivation who are taught using the expository model; (4) Interaction between Project Based Learning Model and Student Motivation on Student Learning Outcomes. This research was conducted at SDN Regency with a population of all fourth grade students as many as 50 students. The sample in this study was class IV A and Class IV B, each of which totaled 25 students. The method used in this study is a quasi-experimental method with a 2x2 factorial design. The data collection instruments used were learning outcome tests, learning motivation questionnaires and project assessment checklists.